What Should Junior Doctors Know about the Drugs they Frequently Prescribe? A Delphi Study among Physicians in the Netherlands. Issue 6 (1st December 2015) - Brinkman, David; Disselhorst, Guus; Jansen, Bernard; Tichelaar, Jelle; van Agtmael, Michiel; de Vries, Theo; Richir, Milan
Abstract: The aim of this study was to identify the information about commonly prescribed drugs that junior doctors should know in order to prescribe rationally in daily practice, defined as essential drug knowledge (EDK). A two‐round Internet Delphi study was carried out involving general practitioners from one practice cluster, and registrars and consultants from two Dutch academic and eight teaching hospitals. A preliminary list of 377 potential EDK items for three commonly prescribed drugs was assessed on a dichotomous scale; an item was considered EDK if at least 80% consensus was reached. The consensus list of EDK items was discussed by the research team to identify similarities between the three drugs, with a view to forming a list of general EDK items applicable to other commonly prescribed drugs. Sixty experts considered 93 of the 377 items (25%) as EDK. These items were then used to form a list of 10 general EDK items. The list of EDK items identified by primary and secondary care doctors could be used in medical curricula and training programmes and for assessing the prescribing competence of future junior doctors. Further research is needed to evaluate the generalizability of this list for other commonly prescribed drugs.